Esther’s Stand Against Injustice: Theology for Women’s Political Participation in Indonesia - Halawa, Iman Kristina; Purwonugroho, Daniel Pesah; Adi, Didit Yuliantono (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
This article is designed with the aim of tracing Esther's example in suing for justice in the face of power. Queen Esther's courage in the Book of Esther, especially her action against King Ahasuerus without an invitation, is a representation of courage against potential injustice. Queen Esther's courage was not blind courage but courage with wise strategy. This study looks at how Esther's actions have affected modern leadership and how courage and wisdom can serve as examples for Christian communities and leaders today. This study can inspire modern leadership to dare to declare an injustice lawsuit against the rulers. The research uses the method of religious research to respond to the injustice in the face of power that threatened the Jewish nation under the rule of King Ahasuerus. The results of this study show that fighting injustice must be accompanied by a wise strategy and trust in God's providence for the Jewish nation by returning to moral principles and values. This research contributes in the form of a theological reflection for Christian women to emulate Esther in facing injustice in Indonesia.